Innovative Enrichment of Service Enterprises Based on the Location of the Regions of Uzbekistan - Nodirovna, Mirzaeva Shirin; o'g'li, Turamuradov Farrukhjon Feruzjon; Asatullayevich, Daminov Bakhodir; o'g'li, Abdukarimov Javokhir Abdumalik (American Journal of Economics and Business Management, 2023)
By innovation factor, we mean the conditions, causes and indicators that affect the intensity and characterization of innovative growth of the enterprise. In this case, the innovation process emerges as a result of the interaction of many factors. This article provides information on innovation enrichment of service enterprises based on the location of the regions of Uzbekistan. In our opinion, the given classifications cover only a small part of the factors influencing the innovative activity of the enterprise. It should be noted that the scientific literature does not identify factors that directly affect innovation. The main purpose of our study is to determine the impact of the activities of industrial enterprises on the efficiency of the regional economy on the basis of the classification of factors influencing the innovative activity of the enterprise.